An ambipolar azaacene as a stable photocathode for metal-free light-driven water reduction. (23rd August 2016) - Gu, Pei-Yang; Wang, Zilong; Xiao, Fang-Xing; Lin, Zongqiong; Song, Rongbin; Xu, Qing-Feng; Lu, Jian-Mei; Liu, Bin; Zhang, Qichun
Abstract : A new ambipolar azaacene has been employed as a photocathode in PEC cells with a current density of 0.13 mA cm −2 at −0.13 V versus RHE. Abstract : Present photoelectrochemical (PEC) cells for water splitting are based on inorganic electrodes. For future large-scale applications, electrodes that are metal-free, of low cost, and with sustainable availability are crucial. Herein, we report a new ambipolar larger azaacene (DQNDN) as a single-active-element-based photocathode in PEC cells with a current density of 0.13 mA cm −2 at −0.13 V versus RHE.